Pan-Cytokeratin Positive Fibroblastic Osteosarcoma of Jaw: An Extremely Rare Entity in a Pediatric Patient. (April 2019) - Urs, Aadithya B; Kumar, Priya; Augustine, Jeyaseelan; Sharma, Pankaj; Narayan, Bhaskar
Osteosarcoma (OS) of jaws is a rare entity characterized by malignant osteoid formation and is most commonly seen in third to fourth decade of life. Here, we present a rare and intriguing case of a 14-year-old pediatric patient, who reported with a chief complaint of swelling in the left maxilla, which was rapidly increasing in size. Both cytokeratin AE1/3 and vimentin-positive spindled cells were seen arranged in storiform pattern with minimal areas of osteoid formation on histopathologic examination. The diagnosis of fibroblastic OS was confirmed by fluorescent in situ hybridization after excluding monomorphic synovial sarcoma. The patient underwent segmental resection of left maxilla and is on close follow-up. A PubMed search revealed that only 5 pediatric cases of fibroblastic OS have been published since 1991. Here, we highlight the diagnostic challenges encountered in reaching the histopathologic diagnosis.